Akibat Hukum Ketiadaan Akta Ikrar Wakaf Atas Perwakafan Tanah - Faisal Faisal (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Waqf land is one of the social services in Islamic religion that is closely related to the law of negativity, meaning as a set of rules governing how to use and use the earth for the common welfare of all the people. The birth of Law No. 41 of 2004 concerning Waqf is a step to reinforce the status of waqf land by providing legal certainty for the land owned by waqf. Based on Government Regulation No. 42 of 2004 concerning Waqf property explained that waqf in its position as one of the institutions of Islamic law, is a religious institution that can be used as a means for the development of religious life. The nature of the research used is a description of the type of empirical juridical. The data sources used in this study are sourced from secondary data consisting of primary legal material, secondary legal material and tertiary law that refers to the problem; how is the legal certainty of waqf on land that does not have a waqf certificate. how are obstacles and legal efforts against waqf on land that does not have a waqf deed. With the issuance of waqf pledge deed by PPAIW, the legal certainty of the waqf land is of legal strength and furthermore it will be even stronger if it has issued its waqf pledge from the National Land Agency Number 422 of 2004 3 SKB/BPN/2004 in Article 1 and Article 2, Law Number 24 of 2004 concerning Agency Endowments Fund.